Comparison of semantics of Indonesian and Malay languages in students’ narrative writings Berunei Darussalam - Sulaeman, Agus; Sjafri, Frimadhona; Hoon, Kim Dong (Edelweiss Applied Science and Technology, 2025)
This study aims to describe and analyze the comparison of the meaning of Malay and Indonesian in the essays of Berunai Darusalam University students who take Malay-Indonesian social and cultural courses at the Malay-Indonesian department of Hankuk University of Foreign Studies Korea. The data in this study is the formation of a new language Idiolect in the term of Indonesian vocabulary. This study has two types of data, namely primary data and secondary data. Primary data in this study is original data obtained through direct interviews. while secondary data in this study are reference books related to the object of research. This type of research is qualitative research. Data collection techniques in this study use observation, interview and documentation techniques. In this study, the method used is the content analysis method. From the results of the study, a comparison of Malay and Indonesian was obtained, the process of differences between Malay and Indonesian in general is a simplification of language forms. For example, morphologically (word structure) and syntax (grammatical structure), tolerance for phonological variations (pronunciation), reduction of a number of functions, and extensive borrowing of words from several languages. In terms of the use of Malay and Indonesian, there are still elements of absorption from Malay which developed from Indonesia, especially Riau Malay, this proves that there is a relationship between Malay and Indonesian.